Pengelolaan Keuangan Keluarga untuk Membangun Ketahanan Keluarga Muslim: Tinjauan dalam Perspektif Ekonomi Islam - Isnani, Sofi Putri; Harnum, Mutiara Puspita; Efendi, Taufik Kukuh; Alfarisy, Fathor Rozy; Firmanda, Muhammad Esza Maulana; Munir, Maryam Bte Badrul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Poverty in Indonesia is a complex problem for the government which is caused by low income levels that lead to economic vulnerability for families. Many Indonesians, who are predominantly Muslim, tend to underestimate household financial management. This study aims to provide an understanding of financial literacy from an Islamic economic perspective, focusing on the financial management of Muslim families to build strong economic resilience and maintain family welfare. This research method is qualitative literature-based research. The study's results show that the financial management of Muslim families is based on the concept of maqashid sharia and avoid elements of usury, maysir, and gharar to achieve both worldly and spiritual well-being. Islamic principles such as mudharabah, musyarakah, ijarah, qardhul hasan, wakalah, and kafalah can be applied to achieve maqashid sharia. Additionally, the Sakinah Finance model can stabilize the finances of Muslim households. The main challenges in family financial management include a lack of transparency and poor communication between family members. Therefore, family asset management can be implemented by maintaining balanced budget allocations, such as for income, needs, desires, education, inheritance, grants, endowments, and emergency funds.